Anlotinib Combined With Chemoradiotherapy Exhibits Significant Therapeutic Efficacy in Esophageal Squamous Cell Carcinoma - Shi, Jingzhen; Zhang, Yingjie; Wang, Jinzhi; Li, Jianbin; Li, Zhenxiang (Frontiers in Oncology, 2020)
Objective: To evaluate the safety and efficacy of anlotinib combined with chemoradiotherapy for treating esophageal squamous cell carcinoma (ESCC) using patient-derived xenografts (PDXs). Methods: PDX-bearing mice were randomly divided into five groups as follows: control group receiving normal saline, the group receiving radiotherapy, the group receiving cisplatin combined with radiotherapy, the group receiving anlotinib combined with radiotherapy and the group receiving anlotinib and cisplatin combined with radiotherapy. Body weights and tumor volumes were measured 3 times weekly for two weeks. The PDXs were initially assessed by comparing the histology of the original patient tumors with that of the corresponding serially passaged xenografts by hematoxylin and eosin (H&E) and P63 staining. Then, expression of Bax, c-PARP, PCNA and CD31 was detected using immunohistochemistry, and apoptosis was detected by a TUNEL assay. Cytokines released into plasma were analyzed using protein chip technology. Finally, two case studies of ESCC patients were presented to further verify the results observed in the PDX models. Results: The pathological characteristics of the serially passaged patient tumor-derived xenografts established in our study were consistent with those of the original ESCC patient samples. The group receiving anlotinib and cisplatin plus radiotherapy exhibited the strongest antitumor response among the groups. Moreover, the ideal anticancer effects of anlotinib combined with chemoradiotherapy observed in clinical patients were consistent with the results observed in the PDX models, and no serious side effects were observed during treatment. Conclusions: Combination therapy with anlotinib and chemoradiotherapy may be an effective regimen for the treatment of advanced ESCC.